Love And Friendship In David Mackay'sten Inch Hero Movie (2011) : An Individual Psychological Approach - Andewi, Anthika Fitri, Dr. Phil. Dewi Candraningrum, M. Ed, Drs. Abdillah. Nugroho, M. Hum (2013)
The major problem of this study is reveal how love and friendship of major characters is reflected in Ten Inch Hero movie directed by David Mackay published in 2011. The objective of the study is to analyze the film based on structural elements and to analyze the film based on individual psychological approach. The object of the study is a movie Ten Inch Hero is directed by David Mackay. The researcher employs the descriptive qualitative research as a type of research. In this method, there are two types of data sources, namely primary data source and secondary data source. The primary data source is the movie itself and the secondary data source is any literature information related to the love and friendship that support the individual psychological analysis. The method of collecting data are watching the movie, reading the movie script, library reviewing and analyzing based on individual psychological approach. The results of the study are as follows. First, based on the structural analysis of the movie, David Mackay as the director of the movie delivers a moral message about the true love and friendship. The structural elements of the movie are related to each other and form a solid unity. Second, based on individual psychological approach, David Mackay tells about the struggle of the major characters to find their love and also friendship.